Didactic and narrative methods of communicating breast cancer screening: a systematic review - Muchiri, Joseph Mutitu (International Journal Of Community Medicine And Public Health, 2019)
There is limited studies that have sought to understanding the processes and mechanisms through which stories influence health-related decisions and actions is critical to maximizing their effectiveness and developing appropriate applications for use in practice settings, more also studies that seek to interrogate the available evidence on the effectiveness of narratives in on seven correlates of behaviour change hence the current review. The main aim of this review was to conduct a comparative evaluation on effectiveness of didactic and narrative methods of cancer communication. Studies were included if they the study used empirical data whether the data was quantitative or qualitative discussing the use of narrative or didactic forms communication on cancer screening, if the study reported outcome of the intervention, if the study was on cancer screening, if the article was written in English language, and the article appeared in a peer-reviewed journal that was published before July 2017. The current systematic review evaluated evidence supporting narrative intervention in cancer communication in an attempt to increase the uptake of breast cancer screening as well as comparing narrative mode of communication with statistical mode of passing the information. Over all it was observed that there exist some evidence that narrative is efficacious in increasing breast cancer screening services. However there were a lot of inconsistences in the evidence adduced in these studies, a fact that warrant that more studies be done in this area of study.